Implementation Value-Based Health Care in Low-Middle Income Countries Healthcare Services: A Scoping Review - Adi Sulistyanto; Puput Oktamianti (Indonesian Journal of Global Health Research, 2025)
Global health expenditure has doubled in the last two decades. Health expenditure in low-middle-income countries accounts for around 4.9% of global GDP, which increases the possibility of out-of-pocket (OOP) payments. The proportion of OOP expenditure in low- and middle-income countries accounts for 40% of total health expenditure. Volume-based service delivery also contributes to this problem; therefore, value-based healthcare (VBHC) is introduced, focusing on increasing patient value through cost efficiency and optimal care outcomes. This study aims to determine the implementation of VBHC in low-middle-income countries. The design study used a scoping review based on the PRISMA-ScR guidelines. Data searches were conducted through Google Scholar, PubMed, SpringerLink, and ScienceDirect, covering publications from January 2019 to April 2024. The initial search identified 1,121 research articles. A total of 11 articles were synthesized in the final review after being adjusted to the research criteria. From 11 articles, originated from Colombia, Africa, India, Sierra Leone, Kenya, Brazil, Lebanon, and Latin America. They were then synthesized based on the six components of the VBHC approach developed by Peter and Teisberg. Organize care into Integrated Practice Units (IPUs) is implemented in 7 articles, measure outcomes and costs for every patient is widely implemented in 10 articles, move to bundled payments for care cycles is only implemented in 2 articles, integrate care delivery across separate facilities is implemented in 7 articles, expand excellent services across geography is only implemented in 4 articles, and build an enabling information technology platform is only implemented in 1 article. The implementation of the VBHC concept in each country takes a different approach but shares a common goal with the VBHC concept: improving patient outcomes while achieving significant cost savings.